2006
DOI: 10.1097/01.brs.0000234735.98075.50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Upright Sitting Postures on Spinal-Pelvic Curvature and Trunk Muscle Activation in a Pain-Free Population

Abstract: Different upright sitting postures resulted in altered trunk muscle activation. Thoracic when compared to lumbo-pelvic upright sitting involved less coactivation of the local spinal muscles, with greater coactivation of the global muscles. These results highlight the importance of postural training specificity when the aim is to activate the lumbo-pelvic stabilizing muscles in subjects with back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
169
2
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(193 citation statements)
references
References 34 publications
11
169
2
11
Order By: Relevance
“…This suggests that tilting the wheelchair seat surface forward enables more efficient one-leg propulsion of a wheelchair with lower activity of the trunk and lower limb muscles. Forward tilt of the pelvis when sitting requires appropriate activity of the lumbar erector spinae, lumbar multifidus, internal oblique, hip flexor, and other muscles 6,7) . By tilting the seat surface forward, the forward tilt moment acts on the pelvis and pelvis backward tilt moment is decreased by the muscle group of the posterior thigh, including the hamstrings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that tilting the wheelchair seat surface forward enables more efficient one-leg propulsion of a wheelchair with lower activity of the trunk and lower limb muscles. Forward tilt of the pelvis when sitting requires appropriate activity of the lumbar erector spinae, lumbar multifidus, internal oblique, hip flexor, and other muscles 6,7) . By tilting the seat surface forward, the forward tilt moment acts on the pelvis and pelvis backward tilt moment is decreased by the muscle group of the posterior thigh, including the hamstrings.…”
Section: Discussionmentioning
confidence: 99%
“…Load on the lower limbs when sitting is ≥25% with forward tilt of the pelvis, about 25% in a neutral position, and ≤25% in a backward tilt 4,5) . Forward tilt of the pelvis when sitting requires appropriate activity of the erector spinae, internal oblique, hip flexor, and other muscles 6,7) . Hemiplegic patients, however, have difficulty tilting the pelvis forward because of decreased trunk function 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, clinicians have tried to employ strategies that make it easier for people with LBP to recruit these muscles. Increased LM activity has been reported when a lumbar lordosis is present which extends throughout the lumbar region to the thoracolumbar junction (Roussouly et al, 2005;O'Sullivan et al, 2006). Claus et al (2009) found that increasing anterior pelvic tilt up to the point of achieving a lordosis up to the thoracolumbar junction resulted in the highest measured activity of both TrA and LM compared to slumped and hyperlordotic (extended into the thoracic spine) postures.…”
Section: Introductionmentioning
confidence: 97%
“…Claus et al (2009) found that increasing anterior pelvic tilt up to the point of achieving a lordosis up to the thoracolumbar junction resulted in the highest measured activity of both TrA and LM compared to slumped and hyperlordotic (extended into the thoracic spine) postures. Therefore, the maintenance of a lumbar lordosis is a cornerstone of specific motor control training (O'Sullivan et al, 2006;Claus et al, 2009;Roussouly et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have been carried out on spinal alignment in upright sitting 17,18) . The data from these studies have become a reference point when considering the desirable spinal alignment of sitting, and the positions they have reported are meaningful for preventing low back pain related to sitting.…”
Section: Introductionmentioning
confidence: 99%